The structure of Trametes versicolor glutathione transferase Omega 3S bound to its conjugation product glutathionyl‐phenethylthiocarbamate reveals plasticity of its active site. (29th April 2019) - Schwartz, Mathieu; Perrot, Thomas; Morel‐Rouhier, Mélanie; Mulliert, Guillermo; Gelhaye, Eric; Didierjean, Claude; Favier, Frédérique
Abstract: Trametes versicolor glutathione transferase Omega 3S (TvGSTO3S) catalyzes the conjugation of isothiocyanates (ITC) with glutathione (GSH). Previously, this isoform was investigated in depth both biochemically and structurally. Structural analysis of complexes revealed the presence of a GSH binding site (G site) and a deep hydrophobic binding site (H site) able to bind plant polyphenols. In the present study, crystals of apo TvGSTO3S were soaked with glutathionyl‐phenethylthiocarbamate, the product of the reaction between GSH and phenethyl isothiocyanate (PEITC). On the basis of this crystal structure, we show that the phenethyl moiety binds in a new site at loop β2 ‐α2 while the glutathionyl part exhibits a particular conformation that occupies both the G site and the entrance to the H site. This binding mode is allowed by a conformational change of the loop β2 ‐α2 at the enzyme active site. It forms a hydrophobic slit that stabilizes the phenethyl group at a distinct site from the previously described H site. Structural comparison of TvGSTO3S with drosophila DmGSTD2 suggests that this flexible loop could be the region that binds PEITC for both isoforms. These structural features are discussed in a catalytic context. Abstract : PDB Code(s):6HPE ;